PENGEMBANGAN MATERIAL SERBUK SILIKA UNTUK IDENTIFIKASI SIDIK JAR! - Christine Elishian; Rosi Ketrin (Jurnal Kimia Terapan Indonesia, 2011)
Development of powder material for fingerprint identification has become Indonesian Department of Safety and Defense priority, especially it was written in the National Research Agenda 2006 -2009. Until now Indonesia still imported thepowder from United States and Japan. Powder fineness is one of the important factors, because finer the powder, more easily it stick to the latent fingerprint and better visualization result will be obtained. In this research, nanosilica was fabricated by used TEOS (tetraethoxysilane) as precursor. Nanosilica is an adhesive material in fingerprint powder while carbon is a coloring agent. In this research nanosilica and carbon black composition was optimized, and the powders were characterized and tried in order to get afingerprint powder which have a better quality to be used by National Police and therefore it can support Indonesian autonomy in safety and defense.Key words: Fingerprint identifier material, nanosilika, TEOS, carbon black